Novel aluminium compounds derived from Schiff bases: Synthesis, characterization and catalytic performance in hydroboration. (2nd January 2019) - Jin, Da; Ma, Xiaoli; Liu, Yashuai; Peng, Jiong; Yang, Zhi
Abstract : Seven novel aluminium complexes supported by Schiff base ligands derived from o ‐diaminobenzene or o ‐aminothiophenol were synthesized and characterized. The reactions of AlMe3 with L 1 ( N, N′ ‐bis(benzylidine)‐ o ‐phenylenediamine) and L 2 ( N, N′ ‐bis(2‐thienylmethylene)‐ o ‐phenylenediamine) gave the complexes L 1 AlMe3 (1 ) and L 2 AlMe2 (2 ), respectively, which involved two types of reaction mechanisms: one was proton transfer and ring closure, and the other was alkyl transfer. Complexes L 3 AlMe2 (HL 3 = 4‐chlorobenzylidene‐ o ‐aminothiophenol) (3 ), L 4 AlMe2 (HL 4 = 2‐thiophenecarboxaldehyde‐ o ‐aminothiophenol) (4 ), L 3 AlH(NMe3 ) (5 ), L 4 AlH(NMe3 ) (6 ) and L 5 AlH(NMe3 ) (HL 5 = 4‐methylbenzylidene‐ o ‐aminothiophenol) (7 ) were prepared by reacting HL 3–5 with equimolar AlMe3 or H3 Al⋅NMe3, respectively. Compounds3 –7 feature an organic–inorganic hybrid containing CNAlSC five‐membered ring. All complexes were characterized using 1 H NMR and 13 C NMR spectroscopy, X‐ray crystal structure analysis and elemental analysis. The efficient catalytic performances of1 –7 for the hydroboration of carbonyl groups were investigated, with compound4 exhibiting the highest catalytic activity among all the complexes. Abstract : Seven novel aluminium complexes were synthesized and fully characterized. All of them displayed excellent catalytic activity in hydroboration reactions.